Synthesis of Potato Starch-Acrylic-Acid Hydrogels by Gamma Radiation and Their Application in Dye Adsorption - Md. Murshed Bhuyan; Nirmal Chandra Dafader; Kazuhiro Hara; Hirotaka Okabe; Yoshiki Hidaka; Md. Mizanur Rahman; Mohammad Mizanur Rahman Khan; Nazia Rahman (International Journal of Polymer Science)
Several kinds of acrylic-acid-grafted-starch (starch/AAc) hydrogels were prepared at room temperature (27°C) by applying 5, 10, 15, 20, and 25 kGy of gamma radiation to 15% AAc aqueous solutions containing 5, 7.5, and 15% of starch. With increment of the radiation dose, gel fraction became higher and attained the maximum (96.5%) at 15 kGy, above which the fraction got lowered. On the other hand, the gel fraction monotonically increased with the starch content. Swelling ratios were lower for the starch/AAc hydrogels prepared with higher gamma-ray doses and so with larger starch contents. Significant promotions of the swelling ratios were demonstrated by hydrolysis with NaOH: 13632±10% for 15 kGy radiation-dosed [5% starch/15% AAc] hydrogel, while the maximum swelling ratio was ~200% for those without the treatment. The authors further investigated the availability of the starch/AAc hydrogel as an adsorbent recovering dye waste from the industrial effluents by adopting methylene blue as a model material; the hydrogels showed high dye-capturing coefficients which increase with the starch ratio. The optimum dye adsorption was found to be 576 mg per g of the hydrogel having 7.5 starch and 15% AAc composition. Two kinetic models, (i) pseudo-first-order and (ii) pseudo-second-order kinetic models, were applied to test the experimental data. The latter provided the best correlation of the experimental data compared to the pseudo-first-order model.